ENHANCING CUSTOMER SATISFACTION THROUGH A WEB-BASED SMARTPHONE REPAIR SERVICE SYSTEM AT WINOV SERVICE - Bagus Deva Pratama, Mohammad; Irawan, Yudie; Setiawan, Arif (Institut Teknologi Nasional Malang, 2025)
The increasing reliance on smartphones has created a demand for efficient repair services. However, many repair businesses still rely on manual processes, causing delays, inefficiencies, and poor customer experiences. This study develops a web-based smartphone repair service system to enhance efficiency, transparency, and customer satisfaction. The system automates repair scheduling, real-time tracking, and customer notifications, minimizing manual intervention. A quantitative research approach was used, collecting data through surveys and system evaluations. Findings show that the system reduces service delays by 35% and improves response time by 42% compared to manual processes. Real-time updates and automated notifications also enhance customer engagement and service transparency. This research contributes to service industries by demonstrating the impact of digital transformation on operational efficiency and customer experience. The results apply not only to smartphone repair services but also to electronics repair, automotive maintenance, and similar sectors requiring efficient service management. These findings offer insights for optimizing digital service frameworks, with potential for further innovation through Artificial Intelligence (AI) integration and blockchain technology for secure service tracking and enhanced transparency.